Factors affecting disease progression in early-stage chronic kidney disease in a multi-ethnic, southeast Asian primary care population - Koh, Hui Qi; Sim, Xueling; Koh, Sky Wei Chee (Frontiers in Medicine, 2025)
BackgroundWhile effective risk factor control and medication optimization in early-stage CKD can significantly slow disease progression, a paucity of studies hinders comprehensive understanding. This study aims to identify factors associated with progression of early-stage CKD in primary care.MethodsWe retrospectively analyzed data of CKD G1-G2 patients with type 2 diabetes or hypertension, recruited from an ongoing cohort between 2017 and 2023 from six polyclinics in Singapore. The outcome of interest was CKD progression, defined as a 25% decline in eGFR from baseline and worsening of CKD stage. Multivariable logistic regression was used to analyze the factors associated with CKD progression among early-stage CKD patients.ResultsAmong 19,274 patients analyzed, CKD progression occurred in 1,992 patients (10.3%). Patients had a mean age of 62.27 years (SD 9.54), 54.4% were male, 70.4% Chinese, 18.1% Malay, 8.2% Indian, and 3.4% Others. On multivariable analysis, factors associated with CKD progression include Malay ethnicity (OR: 1.52, 95% CI: 1.35, 1.72), A2 (OR: 1.41, 95% CI: 1.18, 1.70) and A3 albuminuria (OR: 4.19, 95% CI: 3.45, 5.10), diabetes (OR: 2.59, 95% CI: 2.18, 3.09), hypertension (OR: 1.69, 95% CI: 1.18, 2.41), increasing systolic BP (OR: 1.005, 95% CI 1.001, 1.008), active smoking (OR: 1.26, 95% CI: 1.09, 1.47), being on maximum doses of ACE inhibitors/ARBs at baseline (OR: 1.28, 95% CI 1.07, 1.53) and having undergone CKD counseling (OR: 1.84, 95% CI 1.59, 2.12). Increasing age (OR: 0.991, 95% CI 0.984, 0.998), higher baseline eGFR (OR: 0.968, 95% CI 0.965, 0.972), higher diastolic BP (OR: 0.989, 95% CI 0.983, 0.995), and BMI (OR: 0.981, 95% CI 0.971, 0.991) significantly reduced odds of CKD progression.ConclusionThis study identified key factors associated with early-stage CKD progression in a multi-ethnic Asian population. Further research is also needed to address benefits of patient counseling and SGLT2i use. Refining risk stratification methods will enable targeted interventions and improve outcomes for high-risk CKD patients.